Realising regional potentials through better market integration in China - Molnar, Margit (OECD Publishing, 2019)
China's regions have been experiencing impressive growth over the past decades, but their potentials could be better exploited by creating a single product and labour market. Local protectionism increases transaction costs and hinders competition, thereby taking a toll on productivity. Administrative monopolies have long thrived and are hard to dismantle. Restrictions on the hukou and the fragmented pension system limit labour mobility. Local regulations aim at, among other things, securing the collection of local taxes, without which cities could not afford to offer the same public services to migrants as to urbanites. Hence, dismantling local regulations and creating a single product and labour market needs to go hand-in-hand with the reform of inter-governmental finances. Recent measures on both the product and labour market front appear to aim at making up for the slow progress over the past decade or so.
Keywords: Economics; China, People's Republic